EARLY INITIATION OF BREASTFEEDING IN POSTPARTUM MOTHERS AT PUPUK KALTIM HOSPITAL - Saleha, Siti; Sulastriningsih, Kursih (Homes Journal: Hospital Management Studies Journal, 2022)
Backround: Early Initiation of Breastfeeding (IMD) is placing the baby on his stomach on the mother's chest or abdomen at least one hour immediately after birth. In IMD practice, this skin contact will make the milk come out quickly because more oxytocin is released in the mother's bloodstream. Early Breastfeeding Initiation carried out early provides great benefits in smooth breastfeeding in the first days of the baby's birth, the process of exclusive breastfeeding and can meet the needs of babies up to two years. Objective: To see the description of early breastfeeding initiation in postpartum mothers at the Pupuk Kaltim Hospital, Bontang Method: The purpose of this study was to see the description of early breastfeeding initiation in postpartum mothers at the Pupuk Kaltim Hospital. This type of research is descriptive quantitative. The population in this study were all mothers who gave birth at the Pupuk Kaltim Hospital, Bontang City from April to June, namely 117 people. This study used purposive sampling, with the sampling criteria were mothers who gave birth within a period of 2 months starting from April 1 to June 30, 2021, namely 30 people. Results: Based on the results of the study, it was found that of the 30 postpartum mothers, almost all of them did early initiation of breastfeeding correctly, namely 23 people (76.7%) and a small portion did not correctly initiate early breastfeeding, namely as many as 7 people (23.3%). Conclusion: Based on the results of the research and discussion in the previous chapter, it was concluded that most postpartum mothers had performed IMD correctly.